Clinical Observation and Mechanism Study on the Treatment of Hemiplegic Patients with Foot Drop and Inversion Using the Six Step of Neurological Training Method of Daoyin Technique in Chinese Medicine - Li, Zhong; Wei, Yinghan; Jia, Luyang; Sun, Qiaoying; Peng, Ruijun; Chen, Guangmin; Li, Menglin; Liao, Yanhe; Zhao, Wenru (British Journal of Healthcare and Medical Research, 2024)
Objective: To verify the clinical effect of the innovative six step Daoyin technique method of neurological training in Chinese medicine for the rehabilitation of hemiplegic patients with foot drop and inversion, and explore its mechanism. Method: 64 patients with stroke hemiplegia accompanied by foot drop and inversion during the recovery period were randomly divided into a six-step method group and a control group, with 32 cases in each group, according to the order of hospitalization. The six-step method group adopts of six step Daoyin technique method of the neurological training in Chinese medicine, while the control group adopts the Brunnstrom method and receives rehabilitation training for 4 weeks. Before and after training, Fugl-Meyer score, Lovett muscle strength assessment of tibialis anterior and fibular long and short muscles, as well as joint range of motion assessment of active dorsiflexion and eversion of the foot were conducted, and the data were statistically analyzed. Result: There was no significant difference in various indicators between the two groups before training (P>0.05), and there was a very significant difference in various indicators between the six-step method group after training and before training (P<0.001). There was no significant difference in various indicators between the control group before and after training (P>0.05). There was a significant difference in various indicators between the two groups after training, with P<0.001. The therapeutic effect of the six-step method group was significantly better than that of the control group (P<0.001). Conclusion: The six step Daoyin technique of the neurological training in Chinese medicine is an effective training method for the rehabilitation of stroke hemiplegic foot drop and foot inversion. Its mechanism of action is to use the "motor sensory information motor function coupling" mechanism and "target-dynamics" mechanism formed by the induction of resistance active movement through Daoyin technique to gradually enhance motor sensory information, and feedback this information to the motor center of the cerebral cortex, promoting its synergistic effect, gradually increasing the number and function of activated reserve brain cells, so as to restore lost muscle strength on the basis of restoring brain function, as well as the motor function of dorsiflexion and eversion of the foot, final improving the patient's walking ability.